If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+5)=4(x-2)
We move all terms to the left:
9(x+5)-(4(x-2))=0
We multiply parentheses
9x-(4(x-2))+45=0
We calculate terms in parentheses: -(4(x-2)), so:We get rid of parentheses
4(x-2)
We multiply parentheses
4x-8
Back to the equation:
-(4x-8)
9x-4x+8+45=0
We add all the numbers together, and all the variables
5x+53=0
We move all terms containing x to the left, all other terms to the right
5x=-53
x=-53/5
x=-10+3/5
| 7(x+6)+7x=9x= | | 9(k-4)=4*3k= | | 2+8h=34 | | 8(2w+1)= | | 3^a+1=3^-a+7 | | 4.7x=-7.8 | | 5x+3x-3x=-2 | | 10x-8=56.5 | | 8s−7s=5 | | 12n-n=11n | | 4x+(-8)=-4x-5 | | 3x+7=−8 | | 180+10+20x=130 | | M⁴+4m³+8m²-8m+4=0 | | 3x-7=8x+(-9) | | 180=10+20x+130x | | 130=7+1/3x | | 10+20x+130x=180 | | 10+20x=130x | | 12=12(2/3g+1)+24 | | 8x+2(3x-12)=-26 | | (2n+15)=360 | | 5*1.04^x=12 | | 16c−17c+–9c=20 | | 13/23=4/y | | (4x+9)=6x-29) | | -6(x-9)=-4x+40 | | 3(0)-8y=12 | | 7/a=10/9 | | Y+2=3y4=2y-3 | | n/6=n+6 | | -(-6n+8)=13+3n |